2011
DOI: 10.1007/s12291-011-0126-2
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Gene Polymorphism in Idiopathic Nephrotic Syndrome Children

Abstract: The pathogenesis of idiopathic nephrotic syndrome is not completely understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 28 publications
(32 reference statements)
1
22
0
Order By: Relevance
“…Cytokine genotypes have been studied in patients undergoing solid organ transplantation and certain polymorphisms have been implicated in the development of graft failure/survival . Presently, there are no laboratory assays proficient in predicting the incidence of acute/chronic rejection.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokine genotypes have been studied in patients undergoing solid organ transplantation and certain polymorphisms have been implicated in the development of graft failure/survival . Presently, there are no laboratory assays proficient in predicting the incidence of acute/chronic rejection.…”
Section: Discussionmentioning
confidence: 99%
“…Previously genetic variations of IL-4 and IL-13 and their receptors have been shown to be associated with predisposition to atopy and/or elevated serum IgE levels [100]. Several studies have been conducted to investigate the role of polymorphisms in the genes coding for IL-4, IL-6, and IL-13 in pediatric patients with nephrotic syndrome [74][75][76][101][102][103]. The IL-4 polymorphism rs2243250 was associated with nephrotic syndrome and an increased risk of steroid resistance [74][75][76].…”
Section: Pro-and Anti-inflammatory Factorsmentioning
confidence: 99%
“…Several studies have been conducted to investigate the role of polymorphisms in the genes coding for IL-4, IL-6, and IL-13 in pediatric patients with nephrotic syndrome [74][75][76][101][102][103]. The IL-4 polymorphism rs2243250 was associated with nephrotic syndrome and an increased risk of steroid resistance [74][75][76]. Furthermore, previous research conducted by Jafar et al and Tripathi et al indicate that a genetic polymorphism in the IL-6 gene is associated with decreased responsiveness to steroids [75,76].…”
Section: Pro-and Anti-inflammatory Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some evidence showed association between INS (primary immunologic impairment) and imbalance of Th1 and Th2 subtype as immunoregulator [1,6,7]. In vitro study using peripheral blood mononuclear cell (PBMC) isolated from INS patients showed increase level of various cytokines such as Interleukin (IL)-1 IL-2, IL-4 and tumor necrosis factor (TNF)-α, compared to control group or INS patients at remission state group.…”
mentioning
confidence: 99%